Zinc alloy powder and method of producing the same

The production of zinc alloy powder with specific sieving and atomization conditions addresses filling and fluidity issues, enhancing battery performance through improved filling and discharge characteristics.

JP2025002013APending Publication Date: 2025-01-09DOWA ELECTRONICS MATERIALS CO LTD

Patent Information

Application Number
JP2023101898
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Conventional zinc alloy powders for batteries suffer from insufficient filling properties and fluidity, leading to issues such as clogging during electrode filling and decreased battery capacity due to surface oxidation and oxide film formation.

Method used

The zinc alloy powder is produced with a high percentage passing through a 75 μm sieve (70% by mass) and an apparent density of 3.0 g/cm³, using a disk or gas atomization method in an inert gas atmosphere with limited oxygen content, ensuring spherical shape and minimal oxide film formation.

Benefits of technology

The zinc alloy powder exhibits enhanced filling properties, fluidity, and discharge performance, reducing nozzle clogging and increasing battery capacity and safety by minimizing gas generation and oxide film formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002013000001_ABST
    Figure 2025002013000001_ABST
Patent Text Reader

Abstract

To provide a zinc alloy powder having sufficient charge-ability and fluidity and possessing excellent discharge-ability when used as a negative-pole material for a battery, and a method of producing the same.SOLUTION: A method of producing a zinc alloy powder includes by powdering according to a disk-atomization or gas-atomization process in an atomization atmosphere consisting of inert gas containing oxygen by 10 vol.% or lower using a melt of zinc alloy containing aluminum, bismuth, indium and the remainder of inevitable impurities and zinc, producing a zinc alloy powder that contains aluminum, bismuth, indium and the remainder of inevitable impurities and zinc and has a percentage thereof to pass through a sieve having a mesh size 75 μm of 70 mass% or higher, an apparent density determined in conformity to JIS Z2504 of 3.0 g / cm3 or higher and a fluidity determined in conformity to JIS Z2502 of 40 sec. / 50 g or lower.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a zinc alloy powder and a method for producing the same, and more particularly to a zinc alloy powder used as an anode material for batteries such as alkaline batteries, and a method for producing the same. [Background technology]

[0002] Conventionally, zinc powder, which is relatively inexpensive, has been used as a negative electrode material for batteries such as alkaline dry batteries. As such zinc powder, zinc alloy powder alloyed with elements having high hydrogen overvoltage, such as bismuth, aluminum, indium, gallium, thallium, magnesium, calcium, strontium, cadmium, tin, and lead, has been used.

[0003] In addition, a method has been proposed for producing a zinc alloy powder for alkaline batteries that is inexpensive, has good fluidity (fluidity of 40 to 75 seconds / 50 g as measured by the metal powder fluidity measurement method of JIS Z2502) and prevents clogging of the injection nozzle when filling a gelled zinc negative electrode agent, by using a molten metal obtained by alloying refined molten zinc with an additive metal and atomizing the molten metal using compressed air as a gas source (see, for example, Patent Document 1). Also, a method has been proposed for producing a zinc alloy powder for alkaline batteries that is produced by performing a surface oxidation treatment on zinc alloy powder for alkaline batteries produced by a gas atomization method, so that the bulk density is 3.0 or more, the oxygen concentration is 0.04% by mass or more and less than 0.10% by mass, and the content of particles having a particle size of 75 μm or less is 5% by mass or less as measured by particle size distribution measurement using a 200 mesh sieve (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP-A-9-235636 (paragraph number 0010-0012) [Patent Document 2] JP 2015-106449 A (paragraphs 0007-0022) Summary of the Invention [Problem to be solved by the invention]

[0005] However, although the zinc alloy powder described in Patent Document 1 has improved fluidity, it does not have sufficient packing properties. In addition, the zinc alloy powder described in Patent Document 2 is subjected to a surface oxidation treatment, so that products equivalent to discharge products are generated, and a decrease in capacity as a battery material cannot be avoided by the amount of the products.

[0006] In view of the above-mentioned conventional problems, the present invention aims to provide a zinc alloy powder having sufficient filling property and flowability and excellent discharge property when used as a negative electrode material for a battery, and a method for producing the same. [Means for solving the problem]

[0007] As a result of intensive research to solve the above problems, the inventors of the present invention have achieved a zinc alloy powder having a passing rate of 70% by mass or more through a sieve with an opening of 75 μm, and an apparent density of 3.0 g / cm as determined in accordance with JIS Z2504. 3 By achieving the above, it has been found that it is possible to provide a zinc alloy powder having sufficient packing properties and fluidity and excellent discharge properties when used as a negative electrode material for a battery, by making the flow rate determined in accordance with JIS Z2502 40 seconds / 50 g or less, and thus the present invention has been completed.

[0008] That is, the zinc alloy powder according to the present invention has a passing rate of 70% by mass or more through a sieve with an opening of 75 μm, and an apparent density of 3.0 g / cm3 as determined in accordance with JIS Z2504. 3 or more, and is characterized in that the flowability measured in accordance with JIS Z2502 is 40 sec / 50 g or less.

[0009] The zinc alloy powder preferably contains aluminum, bismuth, and indium, with the balance being inevitable impurities and zinc, and the zinc alloy powder preferably contains 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, and 100 to 1000 ppm of indium. The zinc alloy powder may also contain 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, 100 to 1000 ppm of indium, and 100 ppm or less of calcium or magnesium, with the balance being inevitable impurities and zinc.

[0010] In addition, the method for producing zinc alloy powder according to the present invention is characterized in that a molten zinc alloy is used and pulverized by disk atomization or gas atomization in an inert gas atmosphere containing 10 volume % or less of oxygen.

[0011] In this method for producing a zinc alloy powder, the zinc alloy preferably contains aluminum, bismuth, and indium, with the balance being inevitable impurities and zinc, and the zinc alloy preferably contains 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, and 100 to 1000 ppm of indium. The zinc alloy may also contain 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, 100 to 1000 ppm of indium, and 100 ppm or less of calcium or magnesium, with the balance being inevitable impurities and zinc. The inert gas atmosphere is preferably a nitrogen gas atmosphere. In the case of gas atomization, it is preferable to use a gas atomization method using a confined type gas atomization nozzle.

[0012] The battery according to the present invention is characterized in that the above zinc alloy powder is used as a negative electrode. Effect of the Invention

[0013] According to the present invention, it is possible to provide a zinc alloy powder having sufficient packing property and flowability, and having excellent discharge properties when used as an anode material for a battery, and a method for producing the same. [Brief description of the drawings]

[0014] [Figure 1] 1 is a micrograph of the zinc alloy powder of Example 1. [Diagram 2] 1 is a micrograph of the zinc alloy powder of Example 3. [Diagram 3] 2 is a micrograph of the zinc alloy powder of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In the embodiment of the zinc alloy powder according to the present invention, the ratio of the zinc alloy powder passing through a sieve with an opening of 75 μm is 70 mass % or more, and the apparent density obtained in accordance with JIS Z2504 is 3.0 g / cm 3 or more, and the flowability determined in accordance with JIS Z2502 is 40 sec / 50 g or less.

[0016] The zinc alloy powder preferably contains aluminum, bismuth, and indium, with the balance being inevitable impurities and zinc, and the lead alloy powder preferably contains 1 to 300 ppm aluminum, 60 to 600 ppm bismuth, and 100 to 1000 ppm indium. The zinc alloy powder may also contain 1 to 300 ppm aluminum, 60 to 600 ppm bismuth, 100 to 1000 ppm indium, and 100 ppm or less calcium or magnesium, with the balance being inevitable impurities and zinc.

[0017] The above-mentioned zinc alloy powder embodiments can be produced by the method for producing zinc alloy powder according to the present invention.

[0018] In an embodiment of the method for producing zinc alloy powder according to the present invention, a molten zinc alloy is pulverized by disk atomization or gas atomization in an atomization atmosphere made of an inert gas containing 10 volume % or less of oxygen.

[0019] In the embodiment of the method for producing the zinc alloy powder, the zinc alloy preferably contains aluminum, bismuth, and indium, with the balance being inevitable impurities and zinc, and the zinc alloy preferably contains 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, and 100 to 1000 ppm of indium. The zinc alloy may also contain 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, 100 to 1000 ppm of indium, and 100 ppm or less of calcium or magnesium, with the balance being inevitable impurities and zinc. The inevitable impurities in the zinc alloy may include one or more elements derived from the raw materials, such as lead, iron, cadmium, and copper, at 30 ppm or less.

[0020] In the embodiment of the method for producing zinc alloy powder described above, the atomizing atmosphere is preferably an atmosphere consisting of nitrogen gas containing 10% by volume or less of oxygen, taking into consideration the production cost. By making the oxygen concentration in the atomizing atmosphere 10% by volume or less, the ratio of zinc alloy powder passing through a sieve with an opening of 75 μm can be increased to 70% by mass or more, and zinc alloy powder having a shape close to a sphere can be produced. On the other hand, if the oxygen concentration in the atomizing atmosphere is higher than 10% by volume, an oxide film is generated in the process in which the zinc alloy breaks up from the molten liquid state and solidifies, and due to the influence of this oxide film, the shape of the zinc alloy powder tends to become teardrop-shaped or sweet potato-shaped. Such a complex shape reduces the fluidity of the zinc alloy powder, tends to reduce the apparent density, and tends to reduce the filling property of the gel when producing a battery.

[0021] In the embodiment of the method for producing zinc alloy powder described above, when pulverization is performed by gas atomization, the oxygen concentration in the atomization atmosphere can be maintained at 10% by volume or less by setting the oxygen concentration in the atomization gas released into the atomization atmosphere at 10% by volume or less. When pulverization is performed by disk atomization, if there is no atomization gas released into the atomization atmosphere, the oxygen concentration in the atomization atmosphere can be set at 10% by volume or less. In the case of gas atomization, it is preferable to use a gas atomization method that uses a confined gas atomization nozzle in order to suppress the amount of gas used.

[0022] In the embodiment of the zinc alloy powder, the ratio of the zinc alloy powder passing through a sieve with an opening of 75 μm is 70 mass% or more. That is, when the particle size of the zinc alloy powder is determined by a sieve particle size measurement method (specifically, by sieving the zinc alloy powder, measuring the mass of the zinc alloy powder remaining on the sieve, and calculating the ratio of the zinc alloy powder passing through the sieve by mass percentage), the ratio of particles of 75 μm or less is 70 mass% or more.

[0023] In addition, in the embodiment of the zinc alloy powder, the flow rate measured according to JIS Z2502 is 40 seconds / 50g or less. That is, if 50g of zinc alloy powder is precisely weighed and placed in a funnel, and the time until all of it passes through is measured to determine the flow rate, the flow rate is 40 seconds / 50g or less. If the zinc alloy powder is produced by a conventional air atomizing method or the like, the flow rate will be longer than 40 seconds / 50g, and when a gelled zinc alloy negative electrode is produced using the zinc alloy powder, this is likely to cause problems such as clogging of the injection nozzle when filling the gelled zinc alloy negative electrode agent. In addition, when a zinc alloy negative electrode is produced by applying the zinc alloy powder as a paste, it is preferable that the flow rate is high (the above time is short) in order to obtain a uniform coating surface.

[0024] In addition, in the embodiment of the zinc alloy powder, the apparent density obtained in accordance with JIS Z2504 is 3.0 g / cm 3 More than 3.5g / cm3 When a battery is produced using zinc alloy powder, the volume of the battery is limited, and a higher apparent density allows greater freedom in battery design and can increase the battery capacity.

[0025] In addition, when the above-mentioned zinc alloy powder is used for the manufacture of a primary battery, the smaller the oxide film, the more zinc is utilized as a battery material, which is preferable. The amount of oxygen in the above-mentioned zinc alloy powder can be measured by a non-diffuse infrared absorption method using an oxygen / nitrogen / hydrogen analyzer (e.g., ONH836 manufactured by LECO Japan LLC).

[0026] In the embodiment of the zinc alloy powder described above, it is preferable that the amount of gas generated is small when 5 g of the zinc alloy powder is contacted with 10 g of 40% KOH electrolyte in which 3% zinc oxide (ZnO) is dissolved, and the mixture is allowed to stand at 60°C for 3 days. The amount of gas generated per unit time (gas generation rate) of this zinc alloy powder is mainly the self-corrosion rate of the zinc alloy powder when it is in contact with the electrolyte. If this gas generation rate is high, when the zinc alloy powder is used as the negative electrode of a battery, the zinc alloy powder will react to generate zinc oxide even without applying electricity, which will cause a decrease in the battery capacity and an increase in the internal pressure of the battery, resulting in swelling and leakage.

[0027] In addition, when the above-mentioned zinc alloy powder is used in the negative electrode of a battery, it is preferable to include various elements such as aluminum, bismuth, indium, calcium, magnesium, etc. The composition of this zinc alloy powder can be determined by dissolving the zinc alloy powder in acid and subjecting the solution to ICP atomic emission spectrometry.

[0028] In addition, an LR6 battery (AA alkaline battery) is prepared by mixing the above-mentioned zinc alloy powder embodiment with a gel made by kneading polyacrylic acid as a thickener and a 40% potassium hydroxide (KOH) solution in which 3% by mass of zinc oxide is dissolved as an electrolyte, and using manganese dioxide as a positive electrode. (The battery is placed in an incubator at 20°C, and discharged at 1.5 W for 2 seconds, followed by discharging at 0.65 W for 28 seconds, at a rate of 10 cycles per hour.) In a no-load discharge (high-rate pulse discharge), it is preferable that the time until the closed-circuit voltage reaches 1.0 V is long.

[0029] The above-mentioned zinc alloy powder embodiment can be used not only in primary batteries such as alkaline manganese batteries, but also in secondary batteries (for which research has been progressing in recent years) that use zinc in the negative electrode. In particular, since the zinc alloy powder is mainly fine enough to pass through a 200 mesh sieve and can be used in the negative electrode of a battery, it can be used not only in an inside-out gel-like mass electrode structure such as an alkaline dry battery, but also in a thin-film electrode structure with a spiral structure used in secondary batteries. EXAMPLES

[0030] EXAMPLES Hereinafter, examples of the zinc alloy powder and the method for producing the same according to the present invention will be described in detail.

[0031] [Example 1] First, a zinc alloy containing 50 ppm of aluminum, 400 ppm of bismuth, 500 ppm of indium, with the remainder being inevitable impurities and zinc, was placed in a melting crucible of a rotary disk device and melted at an internal temperature of 570° C. to obtain a molten zinc alloy.

[0032] Next, the stopper installed in the crucible was raised, and the above-mentioned zinc alloy molten metal was dropped and scattered from the injection hole provided at the bottom of the crucible onto a disk rotating at 40,000 rpm, and then rapidly cooled (by disk atomization) in a nitrogen gas atmosphere (oxygen concentration 0.5%) to obtain zinc alloy powder.

[0033] The zinc alloy powder thus obtained was sieved using a standard sieve, and 97% of the powder passed through a 200 mesh (75 μm opening). The apparent density of this zinc alloy powder was measured according to JIS Z2504 and found to be 4.02 g / cm. 3 The flowability of this zinc alloy powder was measured in accordance with JIS Z2502. That is, 50 g of this zinc alloy powder was precisely weighed and placed in a funnel (used in measuring the apparent density), and the time it took for the entire powder to pass through was measured, which was taken as the flowability. As a result, the flowability of this zinc alloy powder was 30 seconds / 50 g. When this zinc alloy powder was observed under a metallurgical microscope, it was found to be a spherical powder, as shown in Figure 1.

[0034] The zinc alloy powder was dissolved in acid and diluted with water, and the composition of the solution was analyzed using an IPC emission spectrometer, which revealed that the zinc alloy powder contained 46 ppm Al, 398 ppm Bi, and 532 ppm In. The zinc alloy powder was also measured by an infrared absorption method using an oxygen / nitrogen / hydrogen analyzer (ONH836 manufactured by LECO Japan LLC), and the ZnO concentration was calculated from the oxygen concentration value obtained, assuming that all the ZnO had become zinc oxide (ZnO), which was 0.08 mass%.

[0035] Furthermore, 5 g of the obtained zinc alloy powder and 10 g of 40% potassium hydroxide (KOH) solution with 3% zinc oxide (ZnO) dissolved therein were placed in a test tube, and liquid paraffin was poured in to fill the test tube, which was then sealed with a stopper (connected to a pipette). The test tube was left to stand in a water bath at 60°C for 3 days, and the amount of liquid paraffin pushed up into the pipette by the gas generated in the test tube was calculated as the amount of gas generated. The amount of gas generated was 114, when evaluated relative to the amount of gas generated in Comparative Example 1 described later, which is set to 100.

[0036] In addition, 1% by mass of polyacrylic acid was added to the obtained zinc alloy powder, and an alkaline solution (40% potassium hydroxide (KOH) solution in which 3% zinc oxide was dissolved) was added to prepare a gelled zinc alloy negative electrode. This gelled zinc alloy negative electrode was used, and manganese dioxide was used as the positive electrode to prepare an LR6 battery (AA alkaline battery). This battery was placed in an incubator at 20°C and subjected to no-load discharge (high-rate pulse discharge). This no-load discharge was performed at a rate of 10 cycles per hour, with a discharge at 1.5 W for 2 seconds followed by a discharge at 0.65 W for 28 seconds. In this no-load discharge, the time until the closed circuit voltage reached 1.0 V was measured, and the time was 124, evaluated relative to the time in Comparative Example 1 described later, which is set to 100.

[0037] [Example 2] A zinc alloy containing 5 ppm aluminum, 300 ppm bismuth, 400 ppm indium, and the remainder consisting of inevitable impurities and zinc was used as the zinc alloy to be melted, and a zinc alloy powder was produced in the same manner as in Example 1, except that the oxygen concentration in the atomizing atmosphere was 3.5%.

[0038] In addition, the percentage of this zinc alloy powder that passed through a 200 mesh (75 μm mesh size), the apparent density, fluidity, composition, ZnO concentration, and amount of gas generated were determined in the same manner as in Example 1, and the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was measured. As a result, the percentage of powder that passed through a 200 mesh (75 μm mesh size) was 98%, and the apparent density was 3.89 g / cm 3 The flow rate was 35 seconds / 50 g, the zinc alloy powder contained 1 ppm Al, 300 ppm Bi, and 408 ppm In, and the ZnO concentration in this zinc alloy powder was 0.06 mass%. The amount of gas generated was 117 when evaluated relative to the amount of gas generated in Comparative Example 1 described later, which will be described later. Furthermore, the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was 121 when evaluated relative to the time in Comparative Example 1 described later, which will be described later.

[0039] [Example 3] A zinc alloy containing 30 ppm aluminum, 150 ppm bismuth, and 200 ppm indium, with the remainder being zinc and unavoidable impurities, was used as the zinc alloy to be melted, and the oxygen concentration in the atomizing atmosphere was set to 8.8%, but the zinc alloy powder was produced in the same manner as in Example 1. As shown in the micrograph of Figure 2, this zinc alloy powder was a powder containing elongated particles in addition to spherical particles. It is believed that such a shape is due to the effect of an oxide film formed by oxygen in the atomizing atmosphere.

[0040] In addition, the percentage of this zinc alloy powder that passed through a 200 mesh (75 μm mesh size), the apparent density, fluidity, composition, ZnO concentration, and amount of gas generated were determined in the same manner as in Example 1, and the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was measured. As a result, the percentage of powder that passed through a 200 mesh (75 μm mesh size) was 73%, and the apparent density was 3.23 g / cm 3 The flow rate was 38 seconds / 50 g, the Al content in the zinc alloy powder was 32 ppm, the Bi content was 147 ppm, the In content was 196 ppm, and the ZnO concentration in this zinc alloy powder was 0.11 mass %. The amount of gas generated was 112 when evaluated relative to the amount of gas generated in Comparative Example 1 described later, which will be described later. Furthermore, the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was 119 when evaluated relative to the time in Comparative Example 1 described later, which will be described later.

[0041] [Example 4] A zinc alloy having the same composition as in Example 1 was prepared, and the molten zinc alloy was used to pulverize the zinc alloy by gas atomization using a confined gas atomization nozzle in an atomization atmosphere in which nitrogen gas and oxygen gas were mixed to an oxygen concentration of 5%, thereby obtaining zinc alloy powder. This zinc alloy powder was a spherical powder, similar to the zinc alloy powder in Example 1.

[0042] In addition, the percentage of this zinc alloy powder that passed through a 200 mesh (75 μm mesh size), the apparent density, fluidity, composition, ZnO concentration, and amount of gas generated were determined in the same manner as in Example 1, and the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was measured. As a result, the percentage of powder that passed through a 200 mesh (75 μm mesh size) was 96%, and the apparent density was 3.65 g / cm 3 The flow rate was 34 seconds / 50 g, the Al content in the zinc alloy powder was 49 ppm, the Bi content was 387 ppm, the In content was 527 ppm, and the ZnO concentration in this zinc alloy powder was 0.08 mass%. The amount of gas generated was 109 when evaluated relative to the amount of gas generated in Comparative Example 1 described later, which will be described later. Furthermore, the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was 117 when evaluated relative to the time in Comparative Example 1 described later, which will be described later.

[0043] [Comparative Example 1] A zinc alloy having the same composition as in Example 1 was prepared, and the molten zinc alloy was pulverized by gas atomization using compressed air in the air as the atomization atmosphere, to obtain zinc alloy powder.

[0044] In addition, the percentage of this zinc alloy powder that passed through a 200 mesh (75 μm mesh size), the apparent density, fluidity, composition, ZnO concentration, and amount of gas generated were determined in the same manner as in Example 1, and the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was measured. As a result, the percentage of powder that passed through a 200 mesh (75 μm mesh size) was 41%, and the apparent density was 2.64 g / cm 3 1 g / cm compared to the example. 3 The degree of filling was low, the fluidity was 72 seconds / 50 g, and more than twice the time required compared to the example was required, and the filling property and fluidity were insufficient. Furthermore, the Al content in the zinc alloy powder was 52 ppm, the Bi content was 396 ppm, and the In content was 522 ppm, and the ZnO concentration in this zinc alloy powder was 0.22 mass%.

[0045] [Comparative Example 2] The zinc alloy powder of Comparative Example 1 was classified using a 200 mesh (75 μm opening) sieve, and the zinc alloy powder that passed through the sieve was collected. A micrograph of this zinc alloy powder is shown in FIG.

[0046] In addition, the percentage of the zinc alloy powder that passed through a 200 mesh (75 μm mesh size), the apparent density, fluidity, ZnO concentration, and amount of gas generated were determined for the recovered zinc alloy powder in the same manner as in Example 1, and the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was measured. As a result, the percentage of the powder that passed through a 200 mesh (75 μm mesh size) was 99%, and the apparent density was 2.68 g / cm 3 1 g / cm compared to the example. 3 The degree of discharging was low, the fluidity was 70 seconds / 50g, and more than twice as long as that of the examples were required, so the filling property and fluidity were insufficient. The ZnO concentration in this zinc alloy powder was 0.24 mass%. The amount of gas generated was 178 when evaluated relative to the amount of gas generated in Comparative Example 1, which was set to 100. Furthermore, the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was 105 when evaluated relative to the time in Comparative Example 1, which was set to 100.

[0047] [Comparative Example 3] A zinc alloy having the same composition as in Example 3 was prepared, and a zinc alloy powder was obtained in the same manner as in Example 1, except that a molten zinc alloy of this zinc alloy was used and the atomizing atmosphere was air.

[0048] In addition, the percentage of this zinc alloy powder that passed through a 200 mesh (75 μm mesh size), the apparent density, fluidity, composition, ZnO concentration, and amount of gas generated were determined in the same manner as in Example 1, and the time required for the closed circuit voltage to reach 1.0 V during no-load discharge of a battery using this zinc alloy powder was measured. As a result, the percentage of powder that passed through a 200 mesh (75 μm mesh size) was 96%, and the apparent density was 1.82 g / cm 3, which was significantly lower than that of the examples, and the fluidity was 78 seconds / 50g, which required more than twice the time compared to the examples, and the filling property and fluidity were insufficient. In addition, the Al in the zinc alloy powder was 34 ppm, the Bi was 151 ppm, and the In was 200 ppm, and the ZnO concentration for this zinc alloy powder was 0.28 mass%. In addition, the amount of gas generated, when evaluated relative to the amount of gas generated in Comparative Example 1 being 100, was 223, which was significantly higher than that of the examples. Furthermore, the time until the closed circuit voltage reached 1.0 V during no-load discharge of the battery using this zinc alloy powder, when evaluated relative to the time in Comparative Example 1 being 100, was 82, which was significantly lower than that of the examples.

[0049] Tables 1 and 2 show the production conditions and properties of the zinc alloy powders of these examples and comparative examples.

[0050] [Table 1]

[0051] [Table 2]

Claims

1. The proportion passing through a sieve with an opening of 75 μm is 70% by mass or more, and the apparent density determined in accordance with JIS Z2504 is 3.0 g / cm 3 and a flowability measured in accordance with JIS Z2502 of 40 sec / 50 g or less.

2. 2. The zinc alloy powder according to claim 1, characterized in that the zinc alloy powder contains aluminum, bismuth, and indium, with the balance being inevitable impurities and zinc.

3. The zinc alloy powder according to claim 2, characterized in that the zinc alloy powder has an aluminum content of 1 to 300 ppm, a bismuth content of 60 to 600 ppm, and an indium content of 100 to 1000 ppm.

4. The zinc alloy powder according to claim 1, characterized in that the zinc alloy powder contains 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, 100 to 1000 ppm of indium, and 100 ppm or less of calcium or magnesium, with the remainder being inevitable impurities and zinc.

5. A method for producing zinc alloy powder, comprising the steps of: using a molten zinc alloy; and pulverizing the molten zinc alloy by disk atomization or gas atomization in an inert gas atmosphere containing 10% by volume or less of oxygen.

6. 6. The method for producing zinc alloy powder according to claim 5, wherein the zinc alloy contains aluminum, bismuth, and indium, with the balance being inevitable impurities and zinc.

7. The method for producing zinc alloy powder according to claim 6, characterized in that the aluminum content in the zinc alloy is 1 to 300 ppm, the bismuth content is 60 to 600 ppm, and the indium content is 100 to 1000 ppm.

8. The zinc alloy according to claim 5, characterized in that the zinc alloy contains 1 to 300 ppm of aluminum, 60 to 600 ppm of bismuth, 100 to 1000 ppm of indium, and 100 ppm or less of calcium or magnesium, with the remainder being inevitable impurities and zinc.

9. 9. The method for producing zinc alloy powder according to claim 5, wherein the inert gas atmosphere is a nitrogen gas atmosphere.

10. 9. The method for producing zinc alloy powder according to claim 5, wherein the gas atomization method is a gas atomization method using a confined type gas atomization nozzle.

11. A battery comprising the zinc alloy powder according to any one of claims 1 to 4 as a negative electrode.

Citation Information

Patent Citations

  • Zinc alloy powder for alkaline battery and its production

    JP1997235636A

  • Zinc alloy powder for alkali batteries and manufacturing method thereof, and alkali battery arranged by use thereof

    JP2015106449A

Cited By

  • Zinc-based composite powder material and preparation method thereof

    CN120055257A